CRAMBE DEVELOPMENT UNDER LIME APPLICATION IN SANDY SOIL - Benetoli da Silva, Tiago Roque; Carraro, Tainara Vanessa; Frigo, Poliana; Alves Barbosa, Natalia; Gurtler Tiburcio, Maria Gabriela; Secco, Deonir; Ferreira Santos, Reginaldo; Zaratin Alves, Charline (Acta Iguazu, 2017)
Crambe (Crambe abssynica Hoechst) is belonging to the Brassicaceae family oilseeds with high oil content, very useful as a feedstock source for biodiesel production. This work was conducted in the Umuarama city, Paraná State, Brazil, in pots containing soil classified as Oxisol typical and aimed to determine dolomitic limestone rates effects (using the V% original, rates to increase the basis saturation to 60, 70, 80 and 90%) on oil content, yield crambe and soil pH. The completely randomized design with four replications was used. Lime application increase the saturation to 70%, provides conditions for higher yields crambe, this makes the ideal pH range to its cultivation soil.